PERSONAL DATA PROTECTION AND LAW ENFORCEMENT AGAINST INFORMATION MANIPULATION ON SOCIAL MEDIA - Rochmadi Wicaksono; Edi Saputra Hasibuan (ANAYASA : Journal of Legal Studies, 2026)
Advances in information and communication technology have brought about significant changes in the use of social media as a means of communication and information exchange in society. However, these advances have also given rise to new legal issues, particularly regarding the protection of personal data and the manipulation of digital information. This study aims to analyze the forms of legal protection for the personal data of social media users based on Indonesian laws and regulations, as well as to examine the effectiveness of law enforcement against information manipulation from a cyberlaw perspective. The research method used is normative legal research employing both a statutory and a conceptual approach. The results show that legal protection for personal data is regulated by the Electronic Information and Transactions Law and the Personal Data Protection Law, which recognize the right to privacy, the obligations of data controllers, and administrative and criminal sanctions for personal data violations. However, implementation still faces various obstacles, such as low levels of digital literacy among the public and limited oversight. Meanwhile, law enforcement against information manipulation on social media has not been effective due to limitations in legal substance, the capabilities of law enforcement officials, and technological challenges such as deepfakes and the borderless nature of the internet. Therefore, it is necessary to strengthen regulations, enhance the capacity of law enforcement officials, and improve the public’s digital literacy to create more effective legal protection in the digital age.